Dynamic Modelling for Planar Extensible Continuum Robot Manipulators - Tatlıcıoğlu, Enver; Tatlıcıoğlu, Enver; Walker, I. D.; Dawson, D. M. (ACTA Press, 2009)
In this paper, a new dynamic model for continuum robot manipulators is derived. The dynamic model is developed based on the geometric model of extensible continuum robot manipulators with no torsional effects. The development presented in this paper extends the previously available models to include a class of extensible continuum robot manipulators. First, the kinetic energy of a slice of the continuum robot is evaluated. Next, the total kinetic energy of the manipulator is obtained by utilizing a limit operation (i.e., sum of the kinetic energy of all the slices). Then, the gravitational potential energy of the manipulator is derived. Next, the elastic potential energy of the manipulator is derived for both bending and extension. Finally, the dynamic model of a planar 3-section extensible continuum robot manipulator is derived by utilizing the Lagrange representation. Numerical simulation results are presented for a planar 3-section extensible continuum robot manipulator.
Keywords: Dynamic modelling; biologically inspired robot manipulators; continuum manipulators; lagrangian